High-loading-capacity small-size PtM / C intermetallic compound, preparation method and application of high-loading-capacity small-size PtM / C intermetallic compound as hydrogen fuel cell cathode catalyst

Through one-step impregnation and two-step calcination processes, high loading, small size and high order PtM/C intermetallic compound catalysts were prepared, which solved the problems of uneven size distribution of the catalyst and high cost in the prior art, and achieved efficient synthesis of the catalyst and excellent electrocatalytic performance.

CN119876682AActive Publication Date: 2025-04-25ANHUI NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411964932.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The prior art is difficult to synthesize PtM/C intermetallic compound catalysts with high loading, small size and high order under high temperature conditions, resulting in uneven distribution of catalyst particles and high cost, which is not suitable for mass production.

Method used

Small-size carbon-carried PtM/C intermetallic compounds with different Pt loads were prepared by one-step immersion and rapid drying, combined with air calcination and slow reduction of medium temperature of argon-hydrogen mixed gas. This method is simple and efficient and can be mass-produced.

Benefits of technology

The catalyst synthesis with high loading, small size and high order degree is achieved, which improves the activity and stability of the catalyst. It is suitable for use in hydrogen fuel cell cathode catalysts and shows excellent half-cell and single-cell performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876682A_ABST
    Figure CN119876682A_ABST
Patent Text Reader

Abstract

The invention provides a high-loading-capacity small-size PtM / C intermetallic compound, a preparation method and application of the high-loading-capacity small-size PtM / C intermetallic compound as a hydrogen fuel cell cathode catalyst.The preparation method comprises the steps that a platinum source, an M metal source and L-cysteine hydrochloride are evenly mixed in a solvent, the obtained solution is dropwise added to carbon black for dipping, and after rapid stirring and drying are conducted, a precursor is obtained; performing air calcination; and then carrying out argon-hydrogen reduction calcination to obtain the product. Compared with the prior art, a medium-temperature slow heating strategy is utilized, the temperature and the heating rate in the reduction process are reduced at the same time, the temperature capable of providing enough energy to overcome an ordering energy barrier is found, and sufficient time is provided for the ordering process of the alloy through slow heating. The PtM intermetallic compound shows excellent electro-catalytic performance, can be used as a cathode catalyst of a hydrogen fuel cell, shows very excellent electro-catalytic activity in half-cell oxygen reduction reaction (ORR) and single-cell test, is simple in synthesis process and has the potential of batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of inorganic nanomaterials and catalyst preparation research, and specifically relates to a high-load small-size PtM / C intermetallic compound, a preparation method and an application thereof as a cathode catalyst for a hydrogen fuel cell. Background Art

[0002] Driven by the "dual carbon" goal, all walks of life are undergoing energy transformation. In order to reduce dependence on fossil fuels and environmental pollution caused by exhaust emissions from traditional fuel vehicles, people are eager to develop new clean energy that can replace fossil energy, such as wind energy, solar energy, tidal energy, hydrogen energy, etc.; among them, hydrogen energy has attracted much attention for its good energy efficiency and high energy density.

[0003] Hydrogen fuel cells are used as an energy conversion device to utilize hydrogen energy to reduce energy pressure and environmental pressure. Hydrogen is used as an energy carrier to undergo oxidation reaction at the anode to obtain H + The electrons diffuse to the cathode through the proton exchange membrane, and the generated electrons form a current from the anode to the cathode through the external circuit, thereby providing energy. Compared with the 2e - In terms of process, the oxygen reduction reaction (ORR) at the cathode is more complicated. - The multi-step coupled process exhibits sluggish kinetics and has a high overpotential; therefore, improving the reaction kinetics of the ORR process becomes the key to the development of proton exchange membrane fuel cells.

[0004] Pt-based catalysts have been proven to be the most effective for the ORR process. However, pure Pt catalysts have strong adsorption of oxygen-containing substances during the ORR process, and the ORR performance is highly dependent on the electronic properties of the catalyst surface. The geometry and electronic structure of the catalyst need to be optimized to improve the utilization of Pt. First, reduce the size of the Pt-based catalyst to expose more active surfaces and thus improve the activity. The particle size of the catalyst should be less than 5nm. Second, form alloys with other transition metals to improve the surface electronic structure and enhance catalytic performance. Intermetallic compounds (IMCs) are also called ordered alloys because they have an ordered structure of near-surface atoms and thermodynamic stability. However, the ordering process of the alloy generally requires high temperatures to overcome the energy barrier of ordered atomic arrangement in the solid phase. High-temperature calcination usually leads to agglomeration of catalyst particles, Ostwald ripening, etc., which makes the size distribution of catalyst particles uneven. Therefore, it is necessary to find a synthesis method and conditions for obtaining highly ordered and small-sized alloy nanoparticles under high temperature conditions.

[0005] In addition, in practical applications, we should not only consider reducing the cost of catalyst production, but also take into account the practical application value. In the production process of membrane electrode (MEA), in order to reduce the thickness of the catalyst layer to ensure a good mass transfer process along the metal conductive interface, the Pt metal loading is usually around 40wt%-50wt%. Since both small size and high order are required at high temperature, the traditional preparation method usually sacrifices metal loading to obtain smaller alloy catalysts, which is not suitable for mass production applications.

[0006] Therefore, it is necessary to provide a catalyst synthesis scheme with high loading, small size and high order. Summary of the invention

[0007] The purpose of the present invention is to provide a high-load small-size PtM / C intermetallic compound and a preparation method thereof, which firstly undergoes rapid drying by one-step impregnation, and then undergoes air calcination and slow reduction at medium temperature in an argon-hydrogen mixed gas to obtain small-size carbon-loaded PtM / C (M=Mn / Fe / Co / Ni and other transition metals) intermetallic compounds (IMCs) with different Pt loadings (40wt%, 50wt%, 60wt%). The present invention combines a one-step impregnation method with a slow heating strategy, and the preparation method is simple and efficient, and can be mass-produced.

[0008] Another object of the present invention is to provide an application of a high-loaded small-sized PtM / C intermetallic compound as a cathode catalyst for a hydrogen fuel cell. The material of the present invention exhibits excellent half-cell and single-cell performance, contributing to the development of fuel cell cathode catalysts.

[0009] The specific technical solutions of the present invention are as follows:

[0010] A method for preparing a high-load small-size PtM / C intermetallic compound comprises the following steps:

[0011] 1) mixing a platinum source, an M metal source and L-cysteine ​​hydrochloride in a solvent, and dropping the obtained solution onto carbon black for impregnation, and drying to obtain a precursor;

[0012] 2) calcining the precursor in air;

[0013] 3) The product after calcination in step 2) is subjected to reduction calcination in an argon-hydrogen atmosphere to obtain a high-load small-sized PtM / C intermetallic compound.

[0014] In step 1), the molar ratio of the platinum source, the M metal source and L-cysteine ​​hydrochloride is 1:1:2-3:1:6; preferably, the molar ratio of the platinum source, the M metal source and L-cysteine ​​hydrochloride is 1:1:2;

[0015] In step 1), the amount ratio of the platinum source to the solvent is 1.9-2.0 mmol / mL;

[0016] In step 1), the platinum source is selected from a soluble platinum salt, preferably chloroplatinic acid hexahydrate H2PtCl6·6H2O;

[0017] In step 1), the solvent is deionized water;

[0018] In step 1), the M metal source is selected from a transition metal source, preferably a Cu source, a Co source or a Ni source;

[0019] Further, in step 1), the M metal source is a soluble transition metal salt, preferably a soluble transition metal nitrate;

[0020] Preferably, the M metal source is selected from a Co source, most preferably cobalt nitrate hexahydrate;

[0021] In step 1), the carbon black is Ketjen black (EC600 JD) with a specific surface area of ​​1400 m 2 / g.

[0022] In step 2), the air calcination process is carried out in a muffle furnace;

[0023] In step 2), the air calcination is specifically as follows: the heating rate is 1-15°C / min, the temperature is raised to calcination temperature 200°C, and the calcination time is 1-6h;

[0024] In step 3), the argon-hydrogen atmosphere reduction calcination process is carried out in a tube furnace;

[0025] In step 3), the volume content of hydrogen in the argon-hydrogen atmosphere is 2-20%;

[0026] In step 3), during the reduction calcination in an argon-hydrogen atmosphere, the heating rate is 2°C / min, the temperature is raised to 700°C, and the calcination time is 2-15h;

[0027] The present invention uses only a simple one-step impregnation and two-step calcination process to prepare a practical catalyst with high metal loading, high order, small size and high quality activity. In the first step of impregnation, in order to ensure that the metal is completely loaded on the carbon black, the present invention configures a high concentration of chloroplatinic acid and cobalt nitrate solution to mix and completely evaporate the solvent water through rapid drying. In the second step of air calcination, carbon-supported metal oxide is obtained, and in the third step of argon-hydrogen calcination, the metal is reduced.

[0028] The present invention provides a high-load small-size PtM / C intermetallic compound, which is prepared by the above method. The high-load small-size PtM / C intermetallic compound is a metal nanoparticle loaded on the surface of carbon black, and the particle size is 2-5nm. The Pt loading in the high-load small-size PtM / C intermetallic compound is 40wt%-60wt%, and the M metal is a transition metal source, preferably Cu, Co or Ni.

[0029] The invention provides an application of a high-loaded small-size PtM / C intermetallic compound as a cathode catalyst for a hydrogen fuel cell.

[0030] The present invention uses a simple one-step synthesis strategy to obtain a series of high-load ordered alloy catalysts with a size of less than 5nm. Compared with traditional disordered solid solutions, Pt-IMC alloy catalysts with ordered atomic arrangement have higher activity and stability, but their synthesis usually requires high-temperature annealing to overcome the energy barrier of atomic migration and ordering, resulting in particle agglomeration. Therefore, it is crucial to find a suitable calcination method to balance the contradiction between the small size and high order of the catalyst. The present invention slowly heats up during the calcination process, and adopts 700°C medium-temperature calcination in the argon-hydrogen mixed gas calcination stage, which provides energy for the alloy catalyst to overcome the ordering energy barrier while giving the alloy catalyst sufficient time for atomic migration and rearrangement. Small-sized nanoparticle metal catalysts have a higher atomic utilization rate, but when the size of the metal nanoparticles is smaller, the surface free energy of the metal will increase, causing the metal nanoparticles to tend to agglomerate, making it difficult to balance the small size of the catalyst with a high metal loading. The present invention adopts a carbon carrier with a high specific surface area to prepare and reduce the catalyst at a medium temperature, and simultaneously utilizes -SH in L-cysteine ​​hydrochloride to form a complex with a metal to avoid particle agglomeration caused by high-temperature calcination.

[0031] Compared with the prior art, the high-load Pt-based IMCs nanocatalyst prepared by the present invention can obtain a highly ordered alloy catalyst under the conditions that the particle size is less than 5nm and the Pt metal loading is greater than 40%. The carbon carrier usually selected needs to have a high surface area, high electronic conductivity, and good resistance to chemical and electrochemical corrosion to ensure that it can accommodate a high metal load, reduce the voltage loss under high current density induced by ohmic impedance, and have good stability, so as to explore conditions for the practical application of fuel cells. The present invention prepares the PtM / C ordered alloy catalyst, and the product is used as a catalyst for the cathode reaction of the fuel cell to reduce the cathode reaction energy barrier and improve the power density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is the X-ray diffraction (XRD) pattern of the carbon-supported metal oxide (product calcined in air) obtained in Example 1;

[0033] Figure 2 is the XRD pattern of the 40% PtCo / C ordered alloy prepared in Example 1;

[0034] Figure 3 This is a high-angle annular dark field scanning transmission (HAADF-STEM) image of the 40% PtCo / C ordered alloy prepared in Example 1;

[0035] Figure 4 This is the mapping diagram of the 40% PtCo / C ordered alloy prepared in Example 1;

[0036] Figure 5 X-ray photoelectron spectroscopy (XPS) of the 40% PtCo / C ordered alloy prepared in Example 1;

[0037] Figure 6 Thermogravimetric analysis (TG) diagram of the 40% PtCo / C ordered alloy prepared in Example 1;

[0038] Figure 7 Cyclic voltammetry (CV) and polarization curve (LSV) diagram of the half-cell oxygen reduction 30k accelerated endurance test of the 40% PtCo / C ordered alloy prepared in Example 1;

[0039] Figure 8 The power density curve of a single cell of 50% PtCo / C ordered alloy prepared in Example 1;

[0040] Fig. 9 is the XRD pattern of the 40% PtCo / C alloy prepared in Comparative Example 1;

[0041] Fig.10 is the XRD pattern of the 40% PtCo / C alloy prepared in Comparative Example 2;

[0042] Fig.11 is the XRD pattern of the 40% PtCo / C alloy prepared in Comparative Example 3;

[0043] Fig.12 XRD patterns of 40% PtCu / C and 40% PtNi / C alloys prepared in Comparative Example 4;

[0044] Fig.13 Cyclic voltammetry (CV) and polarization curve (LSV) of 40% PtCu / C prepared in Comparative Example 4;

[0045] Fig.14 Cyclic voltammetry (CV) and polarization curve (LSV) of 40% PtNi / C prepared in Comparative Example 4;

[0046] Fig.15This is the XRD pattern of the 50% PtCo / C ordered alloy prepared in Example 1. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0049] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0050] The calcination equipment muffle furnace of the present invention is: GMF-1100X—Hefei Kejing; the calcination equipment tube furnace is: OTF-1200X—Hefei Kejing. The carbon black used is Ketjen black (EC600 JD), with a specific surface area of ​​1400m 2 / g.

[0051] Example 1

[0052] A method for preparing a high-load small-size PtM / C intermetallic compound comprises the following steps:

[0053] 1) Preparation of precursor: Chloroplatinic acid hexahydrate, cobalt nitrate hexahydrate and 0.1882 g of L-cysteine ​​hydrochloride were mixed in water, and ultrasonically mixed to obtain a mixed solution, wherein the molar ratio of chloroplatinic acid hexahydrate, cobalt nitrate hexahydrate and L-cysteine ​​hydrochloride was 1:1:2, and the amount ratio of chloroplatinic acid hexahydrate to water was 2.0 mmol / mL. The obtained mixed solution was impregnated with 0.1 g of carbon black, and stirred to evaporate the solvent naturally and dry, to obtain a 40 wt% PtCo / C precursor;

[0054] 2) Air calcination: The precursor obtained after impregnation is placed in a muffle furnace, and the temperature is raised to 200°C at 2°C / min under air atmosphere, and calcined at this temperature for 2h to obtain carbon-supported metal oxides;

[0055] 3) Argon-hydrogen mixed gas reduction: The product after air calcination is introduced into a H2 / Ar mixed gas with a hydrogen volume content of 10% in a tubular furnace, and the temperature is raised to 700°C at 2°C / min for reduction for 2h, and the temperature is naturally cooled to obtain the final product, which is a PtCo / C alloy with a loading of 40wt%.

[0056] The calculation method for the loading of 40wt% is based on the theoretical calculation of the input raw material dosage:

[0057] Loading = [mPt / (mC+mPt+mCo)] × 100%; where mPt is the mass of Pt in the input raw materials, mC is the mass of carbon black, and mCo is the mass of Co in the input raw materials, all in g. Based on the above feed calculation, the loading = 44.23%, which is defined as 40wt% PtCo / C alloy in the present invention.

[0058] The 40wt% PtCo / C alloy prepared according to the above preparation method was characterized by X-ray diffraction (XRD). Figure 1 It was confirmed that the amorphous structure was obtained during the air calcination stage, and the XRD Figure 2 The physical phase was analyzed and the existence of superlattice peaks confirmed that an ordered alloy catalyst was obtained. The size of the nanoparticles was preliminarily calculated to be about 2.3 nm using the Scherrer formula. Figure 3 The ordered arrangement of the two metals was observed and the size distribution of the metal nanoparticles was statistically compared with the results of XRD. Figure 4 The alloy mapping shows that Pt and Co elements are evenly distributed in the same area. Figure 5 The X-ray photoelectron spectroscopy further verifies that the surface of the alloy catalyst contains almost no Cl element, and Pt and Co exist in the form of an alloy. Figure 6 The total metal content was obtained, and combined with the ICP results, the ratio of Pt and Co in the catalyst was determined to be 1:1. The experimental conditions for the thermogravimetric curve TG and the thermogravimetric differential curve DTG were air, 10°C / min, 25°C-800°C.

[0059] The same method as in Example 1 was used, but the amount of raw materials was changed, specifically:

[0060] Hexahydrated chloroplatinic acid, hexahydrated cobalt nitrate and 0.2751g L-cysteine ​​hydrochloride are mixed in water, ultrasonically mixed to obtain a mixed solution, wherein the molar ratio of hexahydrated chloroplatinic acid, hexahydrated cobalt nitrate and L-cysteine ​​hydrochloride is 1:1:2, and the dosage ratio of hexahydrated chloroplatinic acid and water is 2.0mmol / mL, the obtained mixed solution is impregnated in 0.1g carbon black, stirred to make its solvent evaporate naturally and dry, and a 50wt% PtCo / C precursor is obtained; a 50wt% PtCo / C alloy is obtained, and the subsequent air calcination and argon hydrogen mixed gas reduction method are carried out according to the above embodiment 1 to obtain a 50wt% PtCo / C PtCo / C alloy. According to the above-mentioned feeding calculation, the loading = 51.08%, which is defined as a 50wt% PtCo / C alloy in the present invention.

[0061] Comparative Example 1

[0062] The process was carried out according to Example 1, and only the heating rates were changed to 1°C / min, 5°C / min and 10°C / min during the reduction process at 700°C. The XRD results showed that Fig. 9 By observing the change of the superlattice peak, there is no peak of 31.3 degrees at 1°C / min, 5°C / min and 10°C / min, and the ordered structure of the present invention cannot be obtained. Therefore, the present invention controls the heating rate to 2°C / min to prepare it.

[0063] Comparative Example 2

[0064] The same method as in Example 1 was used, except that the calcination temperature was changed to 600°C, 800°C and 900°C during the high-temperature reduction process. Fig.10 Observe the changes in the half-width of the superlattice peak and the diffraction peak. As the calcination temperature increases, the half-width of the catalyst XRD pattern gradually narrows, corresponding to the increase in the size of the alloy nanoparticles; the superlattice peak near 31.3 degrees gradually increases, corresponding to the increase in the order of the alloy. The higher the temperature, the increase in the size of the alloy nanoparticles means the agglomeration of Pt, which will lead to a decrease in the exposed metal surface and a decrease in the catalytic active sites, which is not conducive to obtaining high mass activity and active area, resulting in low utilization of precious metals. Therefore, the present invention controls the temperature to 700°C.

[0065] Comparative Example 3

[0066] The same method as in Example 1 was used to change the molar ratio of Pt to Co in the precursor to 1:3 and 3:1, and then the precursor was calcined in air and reduced at high temperature with argon and hydrogen gas. XRD Fig.11 Observe the changes in the superlattice peaks. The ratio of Pt and Co in the synthesis of intermetallic compounds will affect the degree of alloying and the formation of ordered alloys. Fig.11 As the proportion of Co increases, the alloy peak of XRD shifts to the right from Pt3Co (41.46), PtCo (41.54) to PtCo3 (42.45), indicating that the degree of alloying increases with the increase of Co content. However, the superlattice peak (31.3 degrees) representing the ordered structure does not appear in the XRD diagram of PtCo3, indicating that the formation of ordered alloys requires a specific metal ratio (molar ratio Pt:Co = 1:1 and 3:1).

[0067] Comparative Example 4

[0068] According to Example 1, only the Co source in the precursor is replaced with an equimolar amount of Cu source and Ni source, and then air calcination and argon hydrogen gas high temperature reduction are performed. The obtained products are defined as: 40% PtCu / C and 40% PtNi / C catalysts, and the XRD patterns are as follows: Fig.12 As shown, the product grain size is within 5nm. Therefore, the preparation of small-sized products of the present invention can still be achieved by replacing the metal source with Co source or Cu source.

[0069] Application Example 1

[0070] The application of the high-load small-size PtM / C intermetallic compound provided by the present invention in the half-reaction of hydrogen fuel cells is as follows: the temperature is controlled at 25°C on a Chenhua electrochemical workstation (CHI 760e), and the 40% PtCo / C and 50% PtCo / C catalysts prepared in Example 1 are etched at 90°C for 6h in 0.5M H2SO4 before the electrochemical test (to remove the metal Co on the surface to expose more Pt sites, and at the same time regulate the changes in the surface electronic structure and surface lattice structure of Pt, which is beneficial to improve the catalytic activity), and then washed with deionized water and dried in a 60°C oven for use. A rotating disk electrode (RDE), i.e., a glassy carbon electrode with a diameter of 5mm, is used as a working electrode, an Hg / Hg2SO4 (saturated with K2SO4) electrode and a Pt sheet (5mm×5mm) electrode are used as a reference electrode and a counter electrode, and Hg / Hg2SO4 is calibrated in H2-saturated 0.1M HClO4. All reference potentials have been converted to reversible hydrogen electrode (RHE). The preparation of the working electrode requires the catalyst to be prepared as ink and drop-coated on the surface of the platinum carbon electrode. The isopropanol and Nafion (5wt%, D520) solution is mixed with the catalyst by ultrasonic mixing to prepare an ink with a catalyst concentration of 2mg / mL. The obtained ink is 15μg Pt / cm 2 The loading was drop-coated onto the disk electrode and dried naturally to obtain a uniform thin film electrode. All cyclic voltammetry (CV) and oxygen reduction polarization curves (LSV) were recorded between 0.05 and 1.05 V (vs. RHE) in 0.1 M HClO4. Cyclic voltammetry (CV) scans were performed at 250 m V / s in a 0.1 M HClO4 solution saturated with N2, and the catalyst was electrochemically activated for a certain number of cycles. The capacitive current and electrochemically active area (ECSA) were recorded at 10 mV / s and 50 mV / s, respectively. Then, in 0.1 M HClO4 saturated with O2, the linear sweep voltammetry (LSV) curve was obtained at 1600 rpm and 10 mV / s at a starting potential of 0.05 V, and the final performance was obtained after correction for the capacitive current and solution resistance. The stability of the catalyst was tested and characterized by an accelerated durability test (ADT) in a 0.1 M HClO4 solution saturated with O2. The cycle test was performed in the range of 0.6 to 1.05 V (vs. RHE) with a scan rate of 250 mV / s, and O2 was kept flowing during the test. After the test, the CV curve after ADT and the ORR polarization curve were recorded.

[0071] The prepared 40% PtCo / C catalyst showed a mass activity (MA) of 0.682 A / mg in 0.1 M HClO4 electrolyte in the half-cell RDE test. Pt (0.9V vs.RHE), active area (ECSA) is 73.3m 2 / g Pt The mass specific activity (SA) is 0.930 mA / cm 2 , initially showing excellent oxygen reduction catalytic activity. After the accelerated durability test (ADT) of the 40% PtCo / C catalyst obtained by the present invention, the ECSA lost only 13% and the MA lost only 30%. The mass activities (MA) of the 40% PtCu / C and 40% PtNi / C catalysts were 0.389 A / mg respectively. Pt (0.9V vs. RHE) and 0.286A / mg Pt , active area (ECSA) is 86.1m 2 / g Pt and 83.3m 2 / g Pt , mass specific activity (SA) is 0.451mA / cm 2 and 0.344 mA / cm 2 , initially showing good oxygen reduction catalytic activity. Figure 7 Cyclic voltammetry (CV) and polarization curve (LSV) diagram of the half-cell oxygen reduction of the 40% PtCo / C ordered alloy prepared in Example 1 before and after the 30k accelerated endurance test. Initial represents the initial activity, and 30kADT represents the activity after 30,000 cycles of the accelerated endurance test.

[0072] Application Example 2

[0073] The application of the high-load small-size PtM / C intermetallic compound provided by the present invention in the half-reaction of hydrogen fuel cells is specifically:

[0074] Method: 50% PtCo / C catalyst was added to ionized water, isopropanol and Nafion (D2020) to prepare a uniformly dispersed ink. The ink was sprayed on an active area of ​​25 cm by ultrasonic spraying (XF-100). 2 The anode used commercial PtC; the cathode used the PtCo IMCs catalyst provided by the present invention and TKK (TEC36F52), with a loading of 0.2 g. Pt / cm 2; Catalyst coated membranes (CCMs) were prepared. Nonwoven carbon paper with microporous layers (Sigracet 22BB) was used as gas diffusion layers (GDLs) for the anode and cathode. The performance of the MEA was evaluated on a Scribner 850e potentiostat. The H2-air test was carried out at 80 °C, 100% RH, 150 kPaabs H2 / air, 1 / 4 L min -1 .

[0075] The PtCo IMCs catalyst further exhibited excellent performance in a single cell assembled membrane electrode (MEA). Under the test conditions of hydrogen fuel cell light-duty transportation (LDV; 80°C, 100% RH, 150 kPaabs), the cathode loading was 0.16 g Pt / cm -2 The catalyst obtained by the present invention has a current density of 1.6A / cm at a voltage of 0.65V. -2 , peak power density reaches 1.5W / cm -2 , while the current density of commercial TANAKA (TEC36F52) with the same load is only 1.2A / cm -2 and 0.9W / cm -2 .

[0076] The present invention uses a medium temperature slow heating strategy, while reducing the temperature and heating rate of the reduction process, to find a temperature that can provide enough energy to overcome the ordering energy barrier and slowly increase the temperature to provide sufficient time for the ordering process of the alloy. PtM intermetallic compounds exhibit excellent electrocatalytic performance, can act as cathode catalysts for hydrogen fuel cells, and exhibit very excellent electrocatalytic activity in both half-cell oxygen reduction reaction (ORR) and single-cell tests. The synthesis process is simple and has the potential for mass production.

[0077] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a high-load small-size PtM / C intermetallic compound, characterized in that: The preparation method comprises the following steps: 1) mixing a platinum source, an M metal source and L-cysteine ​​hydrochloride in a solvent, dropping the obtained solution onto carbon black for impregnation, and drying to obtain a precursor; 2) calcining the precursor in air; 3) The product after calcination in step 2) is subjected to reduction calcination in an argon-hydrogen atmosphere to obtain a high-load small-sized PtM / C intermetallic compound.

2. The preparation method according to claim 1, characterized in that: In step 1), the molar ratio of the platinum source, the M metal source and L-cysteine ​​hydrochloride is 1:1:2-3:1:

6.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1), the usage ratio of the platinum source to the solvent is 1.9-2.0 mmol / mL.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step 1), the M metal source is selected from a transition metal source.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step 1), the platinum source is selected from soluble platinum salts.

6. The preparation method according to claim 1, characterized in that: In step 1), the solvent is deionized water.

7. The preparation method according to claim 1, characterized in that: In step 2), the heating rate is 1-15°C / min, and the temperature is raised to calcination temperature 200°C; the calcination time is 1-6h.

8. The preparation method according to claim 1 or 7, characterized in that: In step 3), the volume content of hydrogen in the argon-hydrogen gas is 2-20%; the heating rate is 2° C. / min, and the temperature is raised to calcination temperature of 700° C.; the calcination time is 2-15 hours.

9. A high-load small-size PtM / C intermetallic compound prepared by the preparation method according to any one of claims 1 to 8, wherein the Pt loading is 40wt%-60wt%, and the M metal is a transition metal source, such as Mn, Fe, Co or Ni.

10. An application of the high-load small-size PtM / C intermetallic compound according to claim 9, characterized in that: Application as cathode catalyst in hydrogen fuel cells.

Citation Information

Patent Citations

  • Preparation method of PtCo / C intermetallic compound catalyst with high metal content

    CN114497581A

  • Ultrathin-wall platinum alloy nanotube used as fuel cell catalyst

    CN115360371A

  • S-doped C-loaded PtM intermetallic compound catalyst, preparation method thereof and fuel cell membrane electrode

    CN117712398A

  • PtCu oxygen reduction catalyst with hcp phase ordered structure and preparation method of PtCu oxygen reduction catalyst

    CN119170811A

  • Composite carbon material and method for manufacturing the same, and electrode catalyst and method for manufacturing the same

    JP2013151392A